Primary Posterior Tracheopexy in Esophageal Atresia Decreases Respiratory Tract Infections - van Tuyll van Serooskerken, E. Sofie; Tytgat, Stefaan H. A. J.; Verweij, Johannes W.; Bittermann, Arnold J. N.; Coenraad, Saskia; Arets, Hubertus G. M.; van der Zee, David C.; Lindeboom, Maud Y. A. (Frontiers in Pediatrics, 2021)
Background: Esophageal atresia (EA) is often accompanied by tracheomalacia (TM). TM can lead to severe respiratory complaints requiring invasive treatment. This study aims to evaluate if thoracoscopic primary posterior tracheopexy (PPT) can prevent the potential sequelae of TM in patients with EA. Methods: A cohort study including all consecutive EA patients treated between 2014 and July 2019 at the Wilhelmina Children’s Hospital was conducted. Two groups were distinguished: (group 1) all EA patients born between January 2014 and December 2016 and (group 2) all EA patients born between January 2017 and July 2019, after introduction of PPT. In the latter group, PPT was performed in EA patients with moderate (33-66%) or severe (67-100%) tracheomalacia, seen during preoperative bronchoscopy. Group differences were assessed using the Fisher’s exact test for bivariate variables and the Mann Whitney U-test for continuous variables. Results: A total of 64 patients were included in this study (28 patients in group 1; 36 patients in group 2). In group 2, PPT was performed in 14 patients. Respiratory tract infections (RTIs) requiring antibiotics within the first year of life occurred significantly less in group 2 (61% vs. 25%, p=0.004). Brief resolved unexplained events (BRUEs) seemed to diminish in group 2 compared to group 1 (39% vs. 19%, p=0.09). Conclusion: Thoracoscopic primary posterior tracheopexy decreases the number of respiratory tract infections in EA patients. The clinical impact of reducing RTIs combined with the minimal additional operating time and safety of PPT outweighs the risk of overtreatment.